Global adoption of single-shot targeted intraoperative radiotherapy (TARGIT-IORT) for breast cancer—better for patients, better for healthcare systems - Vaidya, Jayant Sharad; Vaidya, Uma Jayant; Baum, Michael; Bulsara, Max Kishor; Joseph, David; Tobias, Jeffrey S. (Frontiers in Oncology, 2022)
Background: TARGeted Intraoperative radioTherapy (TARGIT-IORT), delivers radiotherapy targeted to the fresh tumour bed exposed immediately after lumpectomy for breast cancer. TARGIT-A trial found TARGIT-IORT to be as effective as whole breast radiotherapy, with significantly fewer deaths from non-breast-cancer causes. This paper documents its worldwide impact and provides interactive tools for clinicians and patients. Method: Centres using TARGIT-IORT provided the date of the first case and the total number of patients. We plotted these data on a customised Google map. An interactive web-based tool provided directions to the closest centre. Using the data from the TARGIT-A trial, we estimated the total savings in travel miles, carbon footprint, and the number of non-breast-cancer deaths that might be prevented. Results: Data from 242 (93%) of the 260 centres treating patients from 35 countries were available. From the first patient treated in 1998 to early 2020, at least 44752 women with breast cancer have been treated with TARGIT-IORT. https://targit.org.uk/travel displays the Google-map of centres with number of cases, and an interactive tool for patients to find the nearest centre offering TARGIT-IORT and their travel savings. Scaling up to the already treated patients, >20 million miles of travel would have been saved, and about 2000 non-breast cancer deaths might be prevented. Conclusion: One can ascertain the number of patients treated with a novel treatment. These data show how widely TARGIT-IORT has now been adopted and gives an indication of its beneficial world-wide impact on a large number of women with breast cancer.